2021
DOI: 10.1007/s00431-021-04136-6
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of endothelial dysfunction and arterial stiffness in multisystem inflammatory syndrome in children

Abstract: Severe acute respiratory syndrome coronavirus 2 infection can result in multisystem inflammatory syndrome in children (MIS-C). MIS-C can lead to myocardial dysfunction, heart failure, and multiorgan failure; the primary finding is hyperinflammation. Endothelial dysfunction has not been evaluated in patients with MIS-C. We investigated endothelial dysfunction and arterial stiffness parameters in patients with MIS-C. The study included 38 pediatric patients (20 males and 18 females aged 4-17 years, mean age 8.89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…In two previous studies [53,54], significantly lower FMD values were reported in COVID-19 patients during the acute phase as compared to healthy adults, with a value of ≤3.43% predicting mortality and longer hospital stay. Similar results were also found in a pediatric population [55]. While these studies focused on the acute phase of the disease, a previous report on 27 COVID-19 patients and 9 controls suggested the presence of persistently impaired FMD three months after virus positivity was given [36].…”
Section: Discussionsupporting
confidence: 77%
“…In two previous studies [53,54], significantly lower FMD values were reported in COVID-19 patients during the acute phase as compared to healthy adults, with a value of ≤3.43% predicting mortality and longer hospital stay. Similar results were also found in a pediatric population [55]. While these studies focused on the acute phase of the disease, a previous report on 27 COVID-19 patients and 9 controls suggested the presence of persistently impaired FMD three months after virus positivity was given [36].…”
Section: Discussionsupporting
confidence: 77%
“…Although COVID-19 infection in children is usually mild, some patients develop MIS-C (multisystem inflammatory syndrome in children), a late complication hallmarked by hyperinflammation, fever and multiorgan dysfunction. Ciftel et al [ 5 ] found that two echocardiography derived arterial stiffness markers (aortic strain and distensibility) were lower in MIS-C versus controls ( p < 0.01). Interestingly, brachial FMD was correlated with markers of arterial stiffness and left ventricular systolic function [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ciftel et al [ 5 ] found that two echocardiography derived arterial stiffness markers (aortic strain and distensibility) were lower in MIS-C versus controls ( p < 0.01). Interestingly, brachial FMD was correlated with markers of arterial stiffness and left ventricular systolic function [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations